Emerging roles of non-coding RNAs in vector-borne infections - Bensaoud, Chaima; Martins, Larissa Almeida; Aounallah, Hajer; Hackenberg, Michael; Kotsyfakis, Michail (Journal of cell science, 2020)
Non-coding RNAs (ncRNAs) are nucleotide sequences that are known to assume regulatory roles previously thought to be reserved for proteins. Their functions include the regulation of protein activity and localization and the organization of subcellular structures. Sequencing studies have now identified thousands of ncRNAs encoded within the prokaryotic and eukaryotic genomes, leading to advances in several fields including parasitology. ncRNAs play major roles in several aspects of vector-host-pathogen interactions. Arthropod vector ncRNAs are secreted through extracellular vesicles into vertebrate hosts to counteract host defense systems and ensure arthropod survival. Conversely, hosts can use specific ncRNAs as one of several strategies to overcome arthropod vector invasion. In addition, pathogens transmitted through vector saliva into vertebrate hosts also possess ncRNAs thought to contribute to their pathogenicity. Recent studies have addressed ncRNAs in vectors or vertebrate hosts, with relatively few studies investigating the role of ncRNAs derived from pathogens and their involvement in establishing infections, especially in the context of vector-borne diseases. This Review summarizes recent data focusing on pathogen-derived ncRNAs and their role in modulating the cellular responses that favor pathogen survival in the vertebrate host and the arthropod vector, as well as host ncRNAs that interact with vector-borne pathogens.
Keywords: interakce hostitele a patogenu; nekódující RNA; Host–pathogen interactions; Vector-borne infection; infekce přenášené vektorem; Host-Pathogen Interactions; zvířata; členovci - vektory; Disease Vectors; eukaryotické buňky; Arthropod Vectors; Non-coding RNAs; Animals; RNA, Untranslated; Eukaryotic Cells